2016
DOI: 10.3390/atmos7040052
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Climate Change on Natural Snow Reliability, Snowmaking Capacities, and Wind Conditions of Ski Resorts in Northeast Turkey: A Dynamical Downscaling Approach

Abstract: Many ski resorts worldwide are going through deteriorating snow cover conditions due to anthropogenic warming trends. As the natural and the artificially supported, i.e., technical, snow reliability of ski resorts diminish, the industry approaches a deadlock. For this reason, impact assessment studies have become vital for understanding vulnerability of ski tourism. This study considers three resorts at one of the rapidly emerging ski destinations, Northeast Turkey, for snow reliability analyses. Initially one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 64 publications
(40 reference statements)
0
18
0
Order By: Relevance
“…hourly resolution and also incorporating air humidity), the separate analysis of natural snow depth and snowmaking potential does not allow for an integrated calculation of snowmelt and total snow depth. Similar non-integrated approaches were applied for Switzerland (Rixen et al, 2011), New Zealand Hreinsson, 2012, Bulgaria, andTurkey (Demiroglu, 2016;Demiroglu, Turp, Ozturk, & Kurnaz, 2016). Pons, López-Moreno, Rosas-Casals, and Jover (2015) integrated snowmaking in an assessment for the Pyrenees, but in their approach snowmaking was only active on days when total snow depth was below a 30 cm threshold.…”
Section: Climate Change Impact and Vulnerability Assessmentsmentioning
confidence: 99%
“…hourly resolution and also incorporating air humidity), the separate analysis of natural snow depth and snowmaking potential does not allow for an integrated calculation of snowmelt and total snow depth. Similar non-integrated approaches were applied for Switzerland (Rixen et al, 2011), New Zealand Hreinsson, 2012, Bulgaria, andTurkey (Demiroglu, 2016;Demiroglu, Turp, Ozturk, & Kurnaz, 2016). Pons, López-Moreno, Rosas-Casals, and Jover (2015) integrated snowmaking in an assessment for the Pyrenees, but in their approach snowmaking was only active on days when total snow depth was below a 30 cm threshold.…”
Section: Climate Change Impact and Vulnerability Assessmentsmentioning
confidence: 99%
“…Resorts with higher levels of vulnerability would need to better assess the potential use and feasibility of snowmaking technology as the main adaptation option in the medium and long term. This type of strategy is very well documented in the consulted literature (e.g., [15][16][17]20,21,42]), which also remarks its potential socio-economic and environmental impact and physical limitations. Taking the example of the resort of Leitariegos, where the artificial snow coverage over total length of runs reaches only 3.9%, the decision on whether invest in snowmaking equipment will benefit from the analysis of climate change impact.…”
Section: Discussionmentioning
confidence: 97%
“…This study showed that snowmaking is currently a very important adaptive tool to deal with climate variability and change, but also remarks the physical limits of current snowmaking technology. Demiroglu et al [17] focused on three resorts located in northeast Turkey by making use of a regional climate model to provide projections of changes in natural snow reliability, snowmaking capacity, and wind conditions under IPCC climate scenario RCP 4.5 and between the periods 1917-2000 and 2021-2050. Results indicate an overall decline in the frequencies of naturally snow reliable days and snowmaking capacities.…”
Section: Introductionmentioning
confidence: 99%
“…The 100 days-principle proposed by Witmer considered that sufficient snow resources were the guarantee for the stability of ski areas, which required 100 days of snow depth above 30 cm annually, and at least 7 of every 10 years [71]. This rule was widely used in subsequent studies [71][72][73][74]. However, the average snow depth of 591 Chinese alpine ski areas and non-operational snow fields varied from 0 cm to 18 cm in the winter, 69% of the ski areas had snow depths of less than 1 cm; 27.7% had snow depths of 1-10 cm, and only 3.3% had snow depths of more than 10 cm.…”
Section: Spatial Distribution Of the Snow Covermentioning
confidence: 99%